Environmental conditions of Borra Cave, Visakhapattanam, India - Bairagya, Haraprasad (International Journal of Environment, 2014)
Caving is an art which can be best experienced in the mystic Borra of Eastern Ghats and ranked as the second largest cave of India just after Belum Caves situated in the same state Andhrapradesh, India. This Cave is fast becoming a hot tourist?s destination offering great adventurous opportunity to the tourists in the Eastern Ghats. The cave is located in the Ananthagiri hills of the Eastern Ghats region near Visakhapattanam and is made of limestone. The emotion of thrill heightens after entering the cave. The entrance has a narrow vertical opening and is well lit. Due to its location in the sub-equatorial region, dripping of water from the cave roofs occurs almost throughout the year. The formation of stalactites and stalagmites create wonderful phenomena specially found in this cave. The conspicuous pillars formed due to the joining of the roof and the floors are an awe-inspiring creativity of the creator of this world. Various viruses and bacteria are in the cave interior along with different other creatures. The Borra cave helps the Govt. of Andhra Pradesh, India, to earn huge economic benefits for the sake of tourism industry. DOI: http://dx.doi.org/10.3126/ije.v3i2.10526 International Journal of the Environment Vol.3(2) 2014: 150-166